Tuning the lability of a series of Ru(II) polypyridyl complexes: a comparison of experimental-kinetic and DFT-predicted reaction mechanisms - Cocic, Dusan; Chrzanowska, Marta; Katafias, Anna; Puchta, Ralph; van Eldik, Rudi (Journal of Coordination Chemistry, 2021)
This report deals with a comparison of experimentally obtained kinetic and activation parameter data, and theoretical DFT computations, in terms of mechanistic information on the water exchange and water displacement reactions by thiourea for a series of complexes of the type [Ru-II(terpy)(N<^>N)(H2O)](2+), where terpy = 2,2 ':6 ',2 ''-terpyridine and N<^>N represents ethylenediamine (en), 2-(aminomethyl)pyridine (ampy), 2,2 '-bipyridine (bipy), 1,10-phenantroline (phen), and N,N,N ',N '-tetramethylethylenediamine (tmen). The complexes were all isolated in the form of [Ru(terpy)(N<^>N)Cl]X (X = Cl- or ClO4-) compounds and fully characterized in both the solid state and in solution. The DFT calculations revealed further mechanistic insight into the water exchange reactions as well as the water displacement reactions by thiourea. Both the experimental activation parameters and the DFT calculations suggest the operation of an associative interchange (I-a) mechanism for both reaction types studied.
CRIS-Team WoS Importer:2021-02-12